Throughput analysis of power beacon-aided multi-hop MIMO relaying networks employing NOMA and TAS/SC - Pham Minh Nam; Thanh-Long Nguyen; Ha Duy Hung; Tran Trung Duy; Nguyen Thanh Binh; Nguyen Luong Nhat (Universitas Ahmad Dahlan, 2022)
This paper measures end-to-end (e2e) throughput of power beacon-assisted multi-hop decode-and-forward (DF) relaying scheme adopting non-orthogonal multiple access (NOMA) and transmit antenna selection (TAS)/selection combining (SC). Particularly, TAS/SC and NOMA are adopted at each hop to relay different data of a source to multiple destinations. Moreover, the transmitters including source and relays have to harvest wireless energy from radio frequency (RF) signals from a power beacon. We also propose a simple and efficient power allocation method for the signals transmitted at each hop. For performance measurement and comparison, we provide closed-form formulas of the e2e throughput over Rayleigh fading channel. We then verify our derivations by computer simulations as well as compare the e2e throughput performance between our scheme and the corresponding one that does not use NOMA.